PENGARUH PERBANDINGAN MEDIA TANAM DAN KONSENTRASI ZAT PENGATUR TUMBUH (ZPT) TERHADAP PERBANYAKAN BENIH KENTANG (Solanum tuberosum L.) G-0 DARI SPROUT - Sumatera Tarigan; Meriksa Sembiring; Roida Ervina Sinaga; Lea Primaret Ketaren (JURNAL AGROTEKNOSAINS, 2021)
This reserch aims to determine the effect of comparison of planting media and and growth regulator concentration on the growth and propagation of G-0 Potato seeds. This research was carried out in the Screen house of the Raya Village garden, Berastagi District, Karo Regency, North Sumatra Province, with a place of ± 1,300 m asl. This research was carried out from January to April 2019. This reserch used the Factorial Randomized Block Design method of two treatment factors, namely the comparison treatment of planting media with the symbol "M" which consists of five levels, namely: without compost (M0 ), 30% compost (M1), 50% compost (M2), 70% compost (M3), and 100% compost (M4). The second factor was giving a growth regulator concentration with the symbol "Z" which consists of three levels, namely: without concentration (Z0), 1.5 ml /L (Z1), and 3 ml / L (Z2). So that 15 treatment combinations were obtained, each treatment was repeated 3 times. The results of the observational data were then analyzed for variance with an F level of 5%. If there is a significant difference (p <0.05), then the test is continued with the Duncan test. The results showed that the treatment comparison of the planting media had a significant effect (p <0.05) on the variable growth in plant height, development of stem diameter, production each sample, and production each plot, and had no significant effect (p> 0.05) on number of branch. The treatment of growth regulator concentration had a significant effect (p <0.05) on production variables each sample, and production each plot, and had no significant effect (p> 0.05) on variable growth in plant height, development of stem diameter, and number of branch.